Distilling senses a journey through art and technology in Asian contemporary art - Pao Pui Lai, Cissy (Hong Kong Arts Centre, 2013)
It gives me great pleasure to welcome you to the Hong Kong Arts Centre (HKAC) 2013 annual flagship exhibition, distilling senses: a journey through art and technology in Asian contemporary art. Celebrating our 36th year, the HKAC, a multidisciplinary arts hub in Hong Kong, continues to play an important role in introducing Asian contemporary arts and setting new trends through cutting-edge exhibitions. Since 2009, we have been dedicated to developing a series of thematic exhibitions, the Annual Flagship Exhibition, and through them we have worked with various Asian curators to promote Asian contemporary arts in Hong Kong. This year we focus on the union between art and technology to discover how they interact and complement each other. This unique series was initiated by Ms Cissy Pao Pui Lai, BBS, who continues to set the theme of this Annual Exhibition, working closely with the HKAC curatorial team.